Sustainability of Agro-Gray Soil to Pollution and Acidification, and its Biodiagnostics - R.N, Ushakov; A.V, Ruchkina; V.I, Levin; O.A, Zakharova; Ya.V., Kostin; N.A, Golovina (International Journal of Engineering and Technology, 2018)
The aim of investigations is to study the resistance of agro-gray heavy loamy soil to heavy metal pollution and acidification on the basis of determining corresponding parameters of buffering, as well as microbiological activity, as a biological diagnosis of fertility potential under stress conditions.The object of investigations is the agro-gray soil of different cultivation degrees: fertile and infertile. In fertile soil, the humus content in barren soil was 2.2-2.5 % and that in fertile soil was 5.4 %.A model of soil resistance to heavy metals and acidification has been developed. The low level of stability of the agro-gray soil appears when the maximum Langmuir adsorption value is less than 91 mM / kg for zinc, less than 104 mM / kg for copper, less than 93 mM / kg for lead, and less than 61 mM / kg for cadmium. The average level of stability is provided for zinc, copper and lead in the range from 91 to 143 mM / kg, 104 - 130 mM / kg and 61 - 132 mM / kg, respectively. A high level of soil stability is guaranteed if the maximum adsorption value exceeds 93 - 143 mM / kg. Â Bio diagnostics included a series of experiments with imitation of pollution and acidification. Soil pollution was modeled by adding 200 and 600 mg / kg of copper to it (experiment 1). In experiment 2, soil was polluted by cadmium at the rate of 10, 30 and 100 MAC. The exposition was 1, 10, 35 and 57 days.Acidification of the soil was simulated by adding dilute sulfuric acid at a rate of 0.018, 0.044, and 0.120 mM / l (experiment 3).In experiment 4, the effect of zinc on the activity of azotobacter in barren and fertile soil was studied. The dose of zinc was 50 and 100 mg / kg.It was established that when the content of humus is not less than 5 %, the average decrease in activity for all groups of microorganisms was not more than 20 % as compared with clean samples. When the humus content was below 3 %, the microbiological activity decreased by more than 30 %.Â Â